Adsorption Concentration of Platinum Metals by Clinoptilolite - T. Ya. Vrublevs'ka; L.V. Vrons'ka; O.Ya. Korkuna; N.M. Matviychouk (Adsorption Science & Technology, 1999)
Ruthenium(IV) and palladium(II) adsorption from aqueous solutions on to Transcarpathian clinoptilolite has been studied under dynamic conditions. The optimum conditions for ruthenium(IV) adsorption from aqueous solutions have been established as follows: pH = 3.5–4.5 or 9.0–11.0; radius of adsorbent particles, 0.200–0.355 mm; and velocity of solution passing through the adsorbent, 3 mm/min. For palladium adsorption from aqueous nitric acid (pH = 4.0) and ammonia (pH = 11.5) solutions, the optimum radius of the adsorbent particles was in the 0.355–0.500 mm range. Desorption of Ru IV and Pd II was performed using 6 M hydrochloric acid. The degree of ruthenium(IV) extraction under optimum conditions was 95% and for palladium(II) extraction from nitric acid and ammonia solutions the corresponding values were 81.5% and 96.8%, respectively.